Teachers’ perspectives towards learning autonomy: a survey on English teachers - Maru, Mister Gidion; Pikirang, Chris Ceasar; Wuntu, Ceisy N (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2021)
This study investigates teachers’ perspective toward autonomous learning in the context of English language learning in the current era. As a mixed research method then analyzing the collected data, it exposed that teachers’ perceptions on learning autonomy is low due to many of whom believed that their learners are still reluctant to take control of their study. It further indicated that, during thisCovid-19 pandemic, a learning autonomy may not be applicable in all context particularly within which school’s facility such as computer library and book library are limited or even not provided. This study concluded that learning autonomy practice is situational.